Progressive rehabilitation — Martabe Gold Mine as a case study - Pearce, S; Orr, M; Grohs, K; Pearce, J (Mine Closure 2016: 11th International Conference on Mine Closure, 2016)
Progressive rehabilitation has been recognised by the mining industry as a key strategy for minimising mine closure costs and environmental risk, with the rehabilitation of potentially acid-forming waste rock being of particular interest due to the very large liabilities associated with sites where this risk has not been properly addressed. When properly implemented as an engineered solution, progressive rehabilitation of potentially acid-forming waste rock can provide an inherently more robust and lower risk rehabilitation strategy compared with the commonly-implemented alternative of an end-of-life waste dump covers. A case study is presented herein where progressive rehabilitation of potentially acid-forming waste rock has been successfully integrated with ongoing construction of the embankment of a tailings storage facility (TSF). The mine site in question, the Martabe Gold Mine in Indonesia, is thought to be unique in that construction of the TSF embankment at the site will require utilisation of almost all of the waste rock to be produced life of mine. The TSF embankment is therefore a fully integrated and engineered structure addressing both tailings and waste rock disposal requirements for the site. This approach offers a number of key benefits, including minimisation of both waste rock rehabilitation and tailings storage costs, and minimising the risk of long-term acid mine drainage. The progressive mine waste rehabilitation strategy adopted by G-Resources at the Martabe Gold Mine was designed taking into account the inherent properties of the waste rock materials, the run-of-mine waste rock schedule, and the engineering constraints required in order to construct a TSF embankment to exacting geotechnical standards. The strategy has required systematic implementation of outcomes reflective of industry leading practice, including: • Detailed waste characterisation studies. • Development of waste characterisation criteria. • Production of a life-of-mine waste schedule. • Selection of a waste sealing specification based on oxidation modelling. • Progressive implementation of selective waste placement and sealing. • Performance measurement to validate design and implementation. All key technical teams at the Martabe Gold Mine, including exploration, mine geology, mine planning, TSF construction and environment, have played an integral role in the implementation of this strategy, which can be described as an integrated waste management solution in which minimisation of mine closure risk is process that is carried out across the life of the mine.
Keywords: waste placement; progressive mine closure; oxygen diffusion